Kulturerbe und Musikwissenschaft : Das musikalische Legat von Dona Nicinha do Samba (1949–2022) - de Oliveira Pinto, Tiago (Die Musikforschung, 2025)
Nicinha do Samba died in February 2022, which raises the question of to what extent a posthumous appreciation of the musical life’s work of this master of samba-de-roda, a genre which was added to the UNESCO Intangible Cultural Heritage list in 2005, can be included in a traditional journal of musicology. Therefore, both the history of musicology and its normative authority to interpret musical styles and genres must be questioned. Epistemic justice as well as gender studies and considerations of musical aesthetics are related to these issues. Finally, the materiality of musical sources and other forms of evidence acquire a new relevance for the comprehension of music as intangible cultural heritage, bringing forth a rather new field of study in music research.